Hepatobiliary disease caused by Henneguya sp. (Cnidaria:Myxozoa) in an Amazonian fish Chaetobranchopsis orbicularis (Characidae) - José Ledamir Sindeaux-Neto; Amanda Queiroz Azevedo; Natalia dos Anjos; Camila Maria Barbosa Pereira; Jhonata Eduard; Michele Velasco (Revista Brasileira de Parasitologia Veterinária)
Abstract The present study describes multifocal infection by Henneguya sp. in the liver and gallbladder of Chaetobranchopsis orbicularis Steindachner 1875, from the Arari River, on Marajó Island, in the Brazilian Amazon. Fifty specimens of C. orbicularis were examined, and after parasitic confirmation, small fragments of the infected organs were removed, fixed in Davidson’s solution, and histologically processed. Multifocal infection in the liver and gallbladder was observed in 56% (28/50) of C. orbicularis specimens. The cysts were full of mature spores with morphological characteristics inherent to the genus Henneguya, with the same morphological and morphometric characteristics: body elongated, ellipsoidal shape in frontal view, and a thick, translucent, birefringent hyaline sheath covering the entire structure of the spore. Histopathological analysis showed cysts with a predominantly fibroblastic capsule, containing spores inside, with a loss of cellular architecture in the liver parenchyma, as well as deformation of the gallbladder mucosal epithelium. Although clinical signs were not observed, the histopathological findings presented alterations that characterize henneguyosis, a microparasitic disease the host, from the Amazon region.